GAMBARAN PROGRAM PEMBINAAN OLAHRAGA PRESTASI CABANG OLAHRAGA SEPAKBOLA DI KONI KABUPATEN SOLOK SELATAN - Diki Putra Ananda; Muhamad Sazeli Rifki (JURNAL STAMINA, 2019)
The problem in this study is that it does not yet know the description development program of football sport achievement in KONI Solok Selatan regancy. The purpose of this study was to determine the supporting and inhibiting factors of the development program of football sport achievment in KONI Solok Selatan regancy. The type of research used is qualitative research. The population in this study were all coaches, members of the management, coaches, officials and players of South Solok Regency, totaling 26 people. The sampling technique is carried out by purposive sampling. Then the sample in this study was administrators totaling 1 person, trainers totaling 1 person and athletes totaling 1 person. The instrument used in this study is an interview then supported by documentation. Based on the results of research on the sports development program of the achievement of the football sports in KONI South Solok Regency, it can be concluded that, 1) Athletes in the development program of football sport achievment in KONI Solok Selatan regancy in terms of enthusiasm for training are high, their efforts to be more accomplished are good and discipline and great motivation from players, 2) The Solok Selatan District football coach already has National coach certification with a background in hobbies and love of football, 3) Training program provided in soccer sports coaching in the South Solok Regency KONI to achieve achievements that are related with physical training, strategy training and technical training, 4) The organization of football sports coaching in KONI Solok Selatan District establishes coordination and cooperation with related parties. Both in terms of activities or events. 5) Facilities and infrastructure in the development of soccer sports in Solok Selatan Regency to support achievement are still inadequate and incomplete and 6) Funding for soccer sports development programs in Solok Selatan Regency is still lacking due to insufficient budget.